Proceedings of the Symposium on Non-Photorealistic Animation and Rendering 2017
DOI: 10.1145/3092919.3092920
|View full text |Cite
|
Sign up to set email alerts
|

Neural style transfer

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Combinations of techniques also merit consideration, such as using edge enhancement from FlowAbs with other techniques, or combining color manipulation with spatial filters. As future work, we also plan to investigate how neural style transfer [Gatys et al 2016;Johnson et al 2016;Semmo et al 2017] can be used to replicate illustrations found in medical textbooks. Such techniques can be quite promising in our context, although their outcome is still hard to control.…”
Section: Limitationsmentioning
confidence: 99%
“…Combinations of techniques also merit consideration, such as using edge enhancement from FlowAbs with other techniques, or combining color manipulation with spatial filters. As future work, we also plan to investigate how neural style transfer [Gatys et al 2016;Johnson et al 2016;Semmo et al 2017] can be used to replicate illustrations found in medical textbooks. Such techniques can be quite promising in our context, although their outcome is still hard to control.…”
Section: Limitationsmentioning
confidence: 99%
“…At the opposite end of the interaction spectrum, most generic example-based methods (e.g., [Bénard et al 2013;Fišer et al 2016]) lack intuitive local control of the style transfer, as discussed by Semmo et al [2017]. Only a few methods targeting a specific task or style, such as hatching illustration [Gerl and Isenberg 2013], offer tools that let the user guide the underlying synthesis algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…However, it was not until the late 20 th century that computers were used to simulate paintings [Hae90]. In the course of following decades, the field of artistic stylization [KCWI13] has significantly developed and extended by learning‐based methods, such as Neural Style Transfers (NSTs) [SID17, JYF * 20]. Even though a large number of image stylization techniques exist, extending these to video remains challenging.…”
Section: Introductionmentioning
confidence: 99%